REAKSI PASAR TERHADAP PERISTIWA STOCK SPLIT DI BURSA EFEK INDONESIA - Purwata, I Putu; Wiksuana, I Gst. Bgs (E-Jurnal Manajemen, 2019)
This study aims to determine the market reaction to stock split events measured by observing the difference in abnormal return (AR) and trading volume activity (TVA) between before and after the stock split event. This study uses an event study approach with an observation period of 10 days before the stock split event, one day the stock split event, and 10 days after the stock split event. Secondary data is obtained on the IDX. The sample in this study were 43 companies that conducted a stock split in 2015 to 2017. The data collection methods used in this study were secondary data in the form of stock prices, joint stock price index and stock trading volume. Furthermore, the hypothesis test used is the Wilcoxon Signed Rank Test using the SPSS version 24 program. The conclusion of this study is that there is a market reaction that occurs, there is a significant difference between the abnormal return (AR) and trading volume activity (TVA) before and after the event stock split. Keywords : market reaction, stock split, abnormal return, trading volume activity.